Fruit Juice Production in Abomey-Calavi and Cotonou Municipalities (Benin): Socio-Professional Profile of Actors and Adoption Level of Hygienic Practices of Enterprises - BABA-MOUSSA, Farid Abdel Kader; Agossou, Noumavo; Messan A. B. Ohin1, Messan A. B. Ohin; Dognon, d’Avila Y; Stéphane K. Houessou1, Stéphane K. Houessou1; Edmond Sacla Aide, Edmond Sacla Aide (My University, 2022)
Fruit juice production sector is developing in Benin’s major cities and appears to have both organisational and technical shortcomings. This study aimed to 1) establish the socio-professional profile of actors in the fruit juice production sector in Abomey-Calavi and Cotonou municipalities and 2) evaluate the adoption level of hygienic practices of enterprises. The methodological approach adopted in this study combined a semi-structured survey with direct observations in fifty enterprises. The statistical analysis was carried out using the R.4.0.0 software. The study revealed that fruit juice enterprises in both municipalities are mainly artisanal (90%) and located in residential areas (94%). They are therefore exposed to contamination risks from domestic and road activities. More than half of these enterprises were created less than five years ago. Three administrative types of enterprises were noted: non-structured (32%), semi-structured (34%) and structured (34%). Almost half of the enterprises belong to at least one professional association. Only a few enterprises have marketing authorization. Women predominate in the positions of director and production assistant. The majority of production managers are men. Most directors and production managers have a university education, but not necessarily in the field of food sciences. The adoption level of hygie significantly influenced by the level of enterprises structuration and size. The level of hygiene in these enterprises is also very weakly influenced by the female gender. Structured and semi-industrial enterprises have a higher adoption level of hygienic practices. Those with acceptable or good hygiene level enterprises contain slightly more women.
Keywords: Fruit Juice; Food Hygiene; Socio-Demographic Profile; Gender; Benin